Endocannabinoids Have Opposing Effects On Behavioral Responses To Nociceptive And Non-nociceptive Stimuli - Torrie Summers (Nature Portfolio, 2017)
Abstract The endocannabinoid system is thought to modulate nociceptive signaling making it a potential therapeutic target for treating pain. However, there is evidence that endocannabinoids have both pro- and anti-nociceptive effects. In previous studies using Hirudo verbana (the medicinal leech), endocannabinoids were found to depress nociceptive synapses, but enhance non-nociceptive synapses. Here we examined whether endocannabinoids have similar bidirectional effects on behavioral responses to nociceptive vs. non-nociceptive stimuli in vivo. Hirudo were injected with either the 2-arachidonoylglycerol (2-AG) or anandamide and tested for changes in response to nociceptive and non-nociceptive stimuli. Both endocannabinoids enhanced responses to non-nociceptive stimuli and reduced responses to nociceptive stimuli. These pro- and anti-nociceptive effects were blocked by co-injection of a TRPV channel inhibitor, which are thought to function as an endocannabinoid receptor. In experiments to determine the effects of endocannabinoids on animals that had undergone injury-induced sensitization, 2-AG and anandamide diminished sensitization to nociceptive stimuli although the effects of 2-AG were longer lasting. Sensitized responses to non-nociceptive stimuli were unaffected 2-AG or anandamide. These results provide evidence that endocannabinoids can have opposing effects on nociceptive vs. non-nociceptive pathways and suggest that cannabinoid-based therapies may be more appropriate for treating pain disorders in which hyperalgesia and not allodynia is the primary symptom.